Останній голова Польського гуртка студентів Київського комерційного інституту Чеслав-Домінік Мадей: реконструкція біографії періоду студентства - Чуткий, Андрій (Europa Orientalis. Studia z Dziejów Europy Wschodniej i Państw Bałtyckich, 2020)
The paper is devoted to studying the student-period part of the biography of the founder of the Polish student group of the Kyiv Commercial Institute Czesław Dominik Madej. The topic is relevant owning to its reconstructing an important period in the biography of one of the leader of the Polish youth movement in Kyiv at the beginning of XX century, being based on archive materials that have been put into scientific circulation for the first time. It helps not only to provide insight into the topic that has not been studied, but also to increase the sources base for studying the Polish community of Ukraine at the begging of XX century. The personality of Madej is of interest from the point of view of breaking ste-reotypes about the leader in the environment of the young generation of Polish patriots in early XX century. He originated from an illiterate family from a town of Sandomierz, all his teenage years he was thirsty for practical knowledge. This desire resulted in a success: after graduating from elementary and secondary schools of Poland, in 1910 Madej enrolled and graduated with flying colours (in 1916) the first higher education establishment of the economic profile in Ukraine – Kyiv Commercial Institute. While being a student of this institute, Madej became head of the Polish group. During this period he was arrested for complicity in a secret meeting of anti-government character (October 1912). Interestingly, the Institutes’s administration effectively covered for him, Thereby, in summer 1914 Madej could make a trip to Italy, resulting in the publication of a number of his first scientific works. His perseverance in education was marked by a difficult fi-nancial situation that Madej experienced that demonstrates how goal-oriented and talented he was. After graduating from the Kyiv Commercial Institute, he began his postgradu-ate studies at this Institute (department of Applied Economics) where he studied until July 1918 and later went to Poland which was approaching to the restoration of its political independence. Besides elucidating all details of his student-period, the number of found out and put into scientific circulation it promotes the studying of other subject matters. Thus, his letter from Italy (summer 1914) provides insight into the character of the economic life and state of economic education in this country, sheds light on the development of tourism industry, etc. And official documents requesting per-mission for abroad trips add interesting details to the life of Kyiv during the First World war period.